Exploring Minor Hockey Players' Knowledge and Attitudes Toward Concussion. Issue 3 (May 2015) - Mrazik, Martin; Perra, Andrea; Brooks, Brian L.; Naidu, Dhiren; Bell, Jeneita M.; Taylor, Christopher A.; Breiding, Matthew J.; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objective: To evaluate minor hockey players' attitudes and knowledge about sport concussions. Participants: Male and female Pee Wee, Bantam, and Midget level players (n = 183) participating in minor hockey and a comparison group of non–hockey players (n = 57). Design: Survey. Main Measures: Player knowledge and attitudes were evaluated with a standardized questionnaire developed for the purpose of this study. Descriptive statistics including cross-tabulations and proportion comparisons were used to report the data. Results: Players had foundational knowledge about concussions; however, more than half underestimated the prevalence and more than 30% were unaware of return to play protocols. Although nearly all players knew what they "should" do when concussed, 33% did not follow recommendations. Players reported more concern and appreciation of the seriousness of concussion than non-players, but they tended to minimize their vulnerability. The most common and helpful information sources were parents, doctors, and coaches, and therefore knowledge translation efforts should target theses audiences. Conclusion: Young athletes continue to demonstrate gaps in their knowledge of concussions. In addition, attitudes toward concussion suggest a developmental trajectory with younger athletes being most likely to ignore current recommended guidelines.